Genes necessary for expression of a virulence determinant and for transmission of Plasmodium falciparum are located on a 0.3-megabase region of chromosome 9. - Day, K P (1993)
Virulence of the human malaria parasite Plasmodium falciparum is believed to relate to adhesion of parasitized erythrocytes to postcapillary venular endothelium (asexual cytoadherence). Transmission of malaria to the mosquito vector involves a switch from asexual to sexual development (gametocytogenesis). Continuous in vitro culture of P. falciparum frequently results in irreversible loss of asexual cytoadherence and gametocytogenesis. Field isolates and cloned lines differing in expression of these phenotypes were karyotyped by pulse-field gel electrophoresis. This analysis showed that expression of both phenotypes mapped to a 0.3-Mb subtelomeric deletion of chromosome 9. This deletion frequently occurs during adaptation of parasite isolates to in vitro culture. Parasites with this deletion did not express the variant surface agglutination phenotype and the putative asexual cytoadherence ligand designated P. falciparum erythrocyte membrane protein 1, which has recently been shown to undergo antigenic variation. The syntenic relationship between asexual cytoadherence and gametocytogenesis suggests that expression of these phenotypes is genetically linked. One explanation for this linkage is that both developmental pathways share a common cytoadherence mechanism. This proposed biological and genetic linkage between a virulence factor (asexual cytoadherence) and transmissibility (gametocytogenesis) would help explain why a high degree of virulence has evolved and been maintained in falciparum malaria.